DOP40 Effectiveness and safety of reference infliximab and biosimilar in Crohn's disease: a French equivalence study. (25th January 2019) - Meyer, A; Rudant, J; Drouin, J; Weill, A; Carbonnel, F; Coste, J
Abstract: Background: CT-P13 is a biosimilar of the reference product (RP) infliximab with demonstrated efficacy and safety in rheumatoid arthritis and spondylarthritis. It has been approved for the treatment of Crohn's disease (CD) based on that experience without specific studies conducted to examine its effects in CD. The aim of the present study was to compare the effectiveness and safety of CT-P13 and the RP in infliximab-naive patients with CD. Methods: This comparative equivalence cohort study was conducted using the nationwide health administrative database (SNDS) which covers more than 99% of the French population (around 65, 000, 000 people) and contains all outpatient (drugs, imaging or endoscopic investigations) and inpatient information (diagnoses, procedures performed and expensive drugs dispensed). Infliximab-naive patients with CD over 15 years of age who started RP or CT-P13 with no other indications for infliximab were included. The primary outcome was a composite endpoint (death, CD-related surgery, all-cause hospitalisation and reimbursement of another biotherapy). Equivalence was defined as a 95% confidence interval (CI) of the hazard ratio (HR) of CT-P13 vs. RP in a multi-variable marginal Cox model situated within the prespecified margins [0.80–1.25]. Results: In total, 5050 patients were included between 1 March 2015 and 30 November 2016 (2551 received RP and 2499 received CT-P13). Patient characteristics at cohort entry were well balanced. Overall, 1147 patients in the RP group and 952 patients in the CT-P13 group met the composite endpoint (including 838 and 719 hospitalisations in RP and CT-P13 groups, respectively). In multi-variable analysis of the primary outcome, CT-P13 was equivalent to RP (HR 0.92; 95% CI: 0.85–0.99). Combination therapy with a thiopurine with (HR 0.71; 95% CI: 0.63–0.80) or without (HR 0.81; 95% CI: 0.73–0.90) prior use of thiopurine was associated with a lower composite event rate. Multi-variable analysis of secondary outcomes did not reveal any significant differences between CT-P13 and RP in terms of the following events: CD-related hospitalisation (HR 1.00; 95% CI: 0.90–1.11), and CD-related surgery (HR 1.09; 95% CI: 0.92–1.28). No differences in safety outcomes were observed between the two groups, (serious infections (HR 0.82; 95% CI: 0.61–1.11), tuberculosis (HR 1.10; 95% CI: 0.36–3.34) and solid or haematological malignancies (HR 0.66; 95% CI: 0.33-1.32). Conclusions: The effectiveness of CT-P13 appears to be equivalent as that of RP for infliximab-naive patients with CD. No difference was observed for safety outcomes.